Estradiol Uses Different Mechanisms in Astrocytes from the Hippocampus of Male and Female Rats to Protect against Damage Induced by Palmitic Acid - Frago, Laura M.; Canelles, Sandra; Freire-Regatillo, Alejandra; Argente-Arizón, Pilar; Barrios, Vicente; Argente, Jesús; Garcia-Segura, Luis M.; Chowen, Julie A. (Frontiers in Molecular Neuroscience, 2017)
An excess of saturated fatty acids can be toxic for tissues, including the brain, and this has been associated with the progression of neurodegenerative diseases. Since palmitic acid (PA) is a free fatty acid that is abundant in the diet and circulation and can be harmful, we have investigated the effects of this fatty acid on lipotoxicity in hippocampal astrocytes and the mechanism involved. Moreover, as males and females have different susceptibilities to some neurodegenerative diseases, we accessed the responses of astrocytes from both sexes, as well as the possible involvement of estrogens in the protection against fatty acid toxicity. PA increased endoplasmic reticulum stress leading to cell death in astrocytes from both males and females. Estradiol (E2) increased the levels of protective factors, such as Hsp70 and the anti-inflammatory cytokine interleukin-10, in astrocytes from both sexes. In male astrocytes, E2 decreased JNK, TNFα and caspase-3 activation. In contrast, in female astrocytes E2 did not affect the activation of JNK or TNFα levels, but decreased apoptotic cell death. Hence, although E2 exerted protective effects against the detrimental effects of PA, the mechanisms involved appear to be different between male and female astrocytes. This sexually dimorphic difference in the protective mechanisms induced by estradiol could be involved in the different susceptibilities of males and females to some neurodegenerative processes.